Rapid and sensitive detection of formaldehyde based on AC electrokinetic effects. (1st January 2018) - Zhang, Jian; Liu, Xin; Wang, Jian; Wu, Jayne; Wang, Chunchang; Qi, Haochen; Liang, Huaguo
Abstract : Formaldehyde is a toxic water‐soluble organic matter. Its detection methods and detection limit have been attracting more attentions. An AC electrokinetic (ACEK)‐enhanced capacitive sensing method for rapid detection of trace formaldehyde in liquid is presented using commercial microelectrode chips. By this method, a detection limit is achieved as low as 0.01 ppm (μg/ml) within a 60 s response time. It is proved that the trace amount of formaldehyde in common solvents can also be effectively detected. As a complement, the capacitance change rate dependence on testing voltage and frequency is investigated. Compared to other existing detection methods, this ACEK‐based capacitive method is a low cost, high sensitive and fast detection means, which shows a great application prospect in industry and research such as food safety and specimen cleaning.